2012
DOI: 10.1104/pp.112.197798
|View full text |Cite
|
Sign up to set email alerts
|

Barley Metallothioneins: MT3 and MT4 Are Localized in the Grain Aleurone Layer and Show Differential Zinc Binding    

Abstract: Metallothioneins (MTs) are low-molecular-weight, cysteine-rich proteins believed to play a role in cytosolic zinc (Zn) and copper (Cu) homeostasis. However, evidence for the functional properties of MTs has been hampered by methodological problems in the isolation and characterization of the proteins. Here, we document that barley (Hordeum vulgare) MT3 and MT4 proteins exist in planta and that they differ in tissue localization as well as in metal coordination chemistry. Combined transcriptional and histologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 65 publications
0
51
1
Order By: Relevance
“…The expression and localization of MTs vary between tissues and organs. In both Arabidopsis (Arabidopsis thaliana) and barley (Hordeum vulgare), MT4 isoforms contribute to the storage and release of Zn 2+ during embryogenesis (Hegelund et al, 2012;Ren et al, 2012 Fig. S4).…”
Section: Suppression Of Zmhbs Affects Somatic Embryogenesismentioning
confidence: 99%
“…The expression and localization of MTs vary between tissues and organs. In both Arabidopsis (Arabidopsis thaliana) and barley (Hordeum vulgare), MT4 isoforms contribute to the storage and release of Zn 2+ during embryogenesis (Hegelund et al, 2012;Ren et al, 2012 Fig. S4).…”
Section: Suppression Of Zmhbs Affects Somatic Embryogenesismentioning
confidence: 99%
“…Over-expression of AtMT4a improved Zn tolerance in A. thaliana mature plants as well [23]. The barley single type 4 metallothionein protein has much higher affinity for Zn binding than for Cd, and is specifically expressed in the embryo and aleurone layer [24]. Over-expressing OsMT1a in rice resulted in increased accumulation of Zn in both leaves and grains [25].…”
Section: Metallothioneinsmentioning
confidence: 97%
“…The metallothionein 4 protein from barley has large Zn-binding capacity and may function in Zn storage in developing and mature grains [24]. Metallothionein 4 is confined to the barley embryo and aleurone layer [24] as well as into Arabidopsis embryos and developing seeds, making type 4 metallothioneins interesting candidates for future Zn biofortification work.…”
Section: Candidates For Future Zn Biofortification Strategiesmentioning
confidence: 99%
“…9.4.1.6.3). It has been reported that MT4 confined to the embryo and aleurone layer in barley grains is involved in preferential Zn binding and functions in Zn storage in developing and mature grains (Hegelund et al 2012). …”
Section: Metallothioneins (Mts)mentioning
confidence: 98%